2002
DOI: 10.1136/gut.51.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acid secretion, gastritis, and mucus thickness on gastric transfer of antibiotics in rats

Abstract: Background and aims: The success of Helicobacter pylori eradication regimens depends on gastric pH, inflammation, and mucus thickness. Our aim was to investigate the effects of acid secretion, inflammation, and mucolysis on gastric antibiotic transfer. Subjects and methods: A total of 134 anaesthetised rats were given metronidazole, amoxicillin, or clarithromycin intravenously and gastric contents were aspirated via an indwelling cannula. Acid secretion was controlled by either omeprazole or pentagastrin while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The anaesthetized rat model provides an opportunity to investigate the mechanisms of gastric antibiotic transfer. In contrast to human studies, no pyloric loss or bile contamination of gastric juice and mucosa occurs, and the gastric transport of novel compounds can be readily evaluated [18] . The blistering method of dissecting the gastric mucosa ensures that the mucosa sample is not contaminated by blood in the micrangium below the gastric mucosa.…”
Section: Amoxicillin Concentration In Gastric Mucosa and The Effect Omentioning
confidence: 99%
See 2 more Smart Citations
“…The anaesthetized rat model provides an opportunity to investigate the mechanisms of gastric antibiotic transfer. In contrast to human studies, no pyloric loss or bile contamination of gastric juice and mucosa occurs, and the gastric transport of novel compounds can be readily evaluated [18] . The blistering method of dissecting the gastric mucosa ensures that the mucosa sample is not contaminated by blood in the micrangium below the gastric mucosa.…”
Section: Amoxicillin Concentration In Gastric Mucosa and The Effect Omentioning
confidence: 99%
“…In the present experiments, three different doses, high (200 mg/kg), middle (100 mg/kg) and low (50 mg/kg), were adopted to avoid the possibility of insufficient dosage, and an animal model was modified according to reported methods [11,18,30] . The anaesthetized rat model provides an opportunity to investigate the mechanisms of gastric antibiotic transfer.…”
Section: Amoxicillin Concentration In Gastric Mucosa and The Effect Omentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we also detected the concentrations of clarithromycin in gastric tissue and serum according to previous studies (10,22). However, the peak area is very small, and detection is not sufficiently sensitive.…”
Section: Discussionmentioning
confidence: 76%
“…It also increased the amoxicillin transfer rate from plasma to gastric aspirate by traversing the gastric mucosa (10). Here, pronase alone exhibited no inhibitory effect on H. pylori, although it has been reported that pronase has an effect on promoting the eradication of H. pylori.…”
mentioning
confidence: 77%